추측을 나타내는 ‘-은가 보-, -은가비-, -은갑-’과 보조형용사 구문 ‘-을까 보-’의 발달 - 고광모(Kwang-mo Ko) (언어학, 2015)
This paper aims at explaining the developments of -unka po-, -unkapi- and -unkap- expressing conjecture and the auxiliary verb construction -ulkka po- in Korean. The po- in -unka po- and -ulkka po- is an auxiliary verb and follows the conjugation pattern of state verbs. It has been generally assumed that the auxiliary state verb po- was originally the action verb po- ‘see', which is transitive. However, this paper takes the position that only intransitive action verbs can change into state verbs. This paper explains that -unka po- has developed from -unka poy- (/poy/), which may be explained as a syntactic blending between the competing constructions -unka sipu- and -e poy-. The poy- in -unka poy- is the passive form of the action verb po- ‘see’ and is an intransitive action verb that means ‘be seen' or ‘appear'. Of course, the development of -unka po- from -unka poy- is an instance of grammaticalization. The crucial step in this grammaticalization process was the change of poy- into a state verb. This change was undoubtedly accompanied by semantic abstraction. The change of poy-＞po- is explained as follows. As the result of the above-mentioned semantic abstraction speakers became unaware of the reason why the marked form poy- should be used and they replaced it with the unmarked form po-. Examples of similar replacement are not so rare in Korean. In some dialects -unka poy- became -unkapi- by a series of phonological changes. Further, in some dialects -unkapi- became -unkap- by syncope before consonant-initial endings. The shape of -unkap shows that the coalescence of -unka poy- has been completed. The auxiliary verb construction -ulkka po- is interpreted to have developed from -ulka poy-, which may have begun to be used under the analogical influence of -unka poy-. It is believed that the developmental process of -ulkka po- was parallel to that of -unka po-, and that -ulkka po- was originally used to express conjecture only. The various usages of -ulkka po- are interpreted to have been derived from expressing conjecture. KCI Citation Count: 2